SOCIOLINGUISTIC FACTORS THAT IMPACT THAT STUDENTS’ LANGUAGE LEARNING - Jabborova Madinabonu (Web of Journals Publishing, 2024)
The research includes social factors that impact language learning. It considers the learning environment and the characteristics of the learners from a sociolinguistic perspective. Various sociolinguistic terms are used to describe the proficiency, acquisition, and use of language by learners in society. In this term, we gained a mass of valuable information from several articles. The articles that explore sociolinguistics and its various aspects enhance our comprehension of language usage in society. Teachers consider the sociolinguistic factors of learners and find methods, approaches, and techniques in a classroom. Having knowledge of sociolinguistics enhances communication effectiveness and fosters the learning process. In this research, the groups are divided into subgroups based on gender and ethnic factors. It  briefly describes these subgroups and  appropriate pedagogical implications. Understanding sociolinguistic factors is crucial for teachers and learners as it allows them to grasp the impact of language variations and social identity, multilingualism and language context, regional, ethnic, and social factors on language use and language policy, all of which contribute to effective communication skills. Incorporating social network and solidarity theories is essential in sociolinguistics in order to foster social connection and respect for different dialects and variations. Additionally, developing sociolinguistic competence and a positive language attitude are important for using language appropriately in various social settings.
Keywords: sociolinguistic factors, pedagogical implications, ethnicity, cultural norms socioeconomic status, gender.